Synchronous PWM Regulation of Inverters of Drive Installation with Two Stator Windings of Electrical Motor - Oleschuk V. (Problems of the Regional Energetics)
The aim of this work is to modernize schemes and algorithms of synchronous control and modulation for two-inverter based system for ac drive with dual stator windings of electric motor, in order to provide improved harmonic composition of its stator winding voltage. This goal is achieved by including in the control scheme of the system of functional dependencies linking voltage magnitude on stator windings of motor with the corresponding pole voltages of two inverters controlled by algorithms of synchronous multi-zone pulsewidth modulation (PWM), as well as by including in control scheme of current values of specialized phase shift between control signals of two inverters. It has been shown (and it is one of the basic contribution) that in two-inverter-based system with the developed control strategy voltage at stator windings of electric motor is characterized by a quarter-wave symmetry, and even-order harmonics, as well as subharmonics (of the fundamental frequency of system), are lacking in its spectra, including cases of control modes with fractional relationships between the switching frequency of converters and the output frequency of system. Results of determination of weighted total harmonic distortion factor of voltage waveforms show that at low and average values of modulation index of converters algorithms of continuous multi-zone modulation assure better integral spectral characteristics of voltage at stator windings of motor. In the case of increased values of modulation index of converters, improved spectral characteristics of voltage at stator windings of motor are achieved by the using of algorithms of discontinuous multi-zone modulation.